Ultrahigh radiation resistance of nanocrystalline diamond films for solid lubrication in harsh radiative environments. (September 2021) - Xu, Jiao; Dai, Jun; Ren, Fuzeng; Wang, Yongfu; Wang, Peng; Xu, Shusheng; Wu, Sudong; Lin, Jianjun; Yang, Yun; Guo, Dengji; Wang, Xujin
Abstract: In this study, different types of carbon films, including diamond-like carbon (DLC), fullerene-like carbon (FLC), and nanocrystalline diamond (NCD) films, were studied in detail. The film structural and property changes before and after heavy-ion irradiation with increased displacement damage were investigated. The results reveal that radiation-induced structural changes result in heavily degraded lubricant properties of DLC and FLC films but can help improve the lubricant properties of NCD films. The displacement damage of 2.0 dpa was a threshold parameter above which the nanocomposite NCD films stepped into a quasi-saturation state to create an amorphous structure with an ultralong lifetime (more than 6.0 × 10 5 cycles) and excellent antiwear properties (magnitude of 10 −7  mm 3 /N‧m), which is of great importance for the application of NCD films in nuclear reactors. The radiated NCD films could produce tribofilms configured in an amorphous structure, which provided superior lubricant properties to the graphitic tribofilms of DLC and FLC films. The results also contribute to a novel principle for prolonging the lifetime of solid lubricant films in ion-radiation environments, based on the significant tribological properties of the radiation-produced amorphous layer in a quasi-saturation state. Graphical abstract: Image 1 Highlights: Heavy-ion irradiation is beneficial in improving lubricant properties of NCD films. Quasi-saturated NCD films exhibit excellent anti-wear properties than DLC films. Radiated NCD films produce amorphous tribofilms with good antiwear properties. A novel principle prolongs the lifetime of NCD films in irradiation environments.